ТЕКСТЫ С ФОНОСТИЛИСТИЧЕСКИМИ ФОНОВАРИАНТАМИ И ИХ ПЕРЕВОД ( НА МАТЕРИАЛЕ УЗБЕКСКОГО ЯЗЫКА) - Гафуров, Б.З. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the phonographic design of phonovariants of nouns in the Uzbek language when translating them into Russian. The practical material is presented by extrats from works of fiction in Uzbek literature.
Keywords: noun; phonovariants; stylistic coloring; language; colloquial speech